Penerapan Arsitektur Hijau Pada Ruang Publik Waduk Tunggu Bitoa Kota Makassar - Pradana, Lae Alexander; Marwati, Marwati; A'raaf Tauhid, Fahmyddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
Public space is one of the city's quality indices that functions as an interaction space, a container for corridors, and a place for street vendors to sell their wares. This is even though the area around the bridge is a route often passed by the general public. The surrounding community also uses the reservoir for fisheries by utilizing the tidal area around the pool to plant wild plants during the rainy season, and this causes further damage to the banks of the reservoir. This study aims to design the Waiting Bitoa Reservoir Public Space in Makassar City to be an excellent environmental facility with a Green Architecture approach. The importance of green architecture is used to support the natural environment by having several principles, such as utilizing energy, meeting the needs of building users, being environmentally friendly, and adapting to the local climate. A qualitative descriptive method of the existing field data is synthesized into a design form. The results of the application of green architecture are applied to landscapes, open space systems, and natural materials in building units